Acetate ameliorates nephrotoxicity in streptozotocin-nicotinamide-induced diabetic rats: Involvement of xanthine oxidase activity. (June 2021) - Olaniyi, Kehinde S.; Amusa, Oluwatobi A.; Akinnagbe, Nifesimi T.; Ajadi, Isaac O.; Ajadi, Mary B.; Agunbiade, Toluwani B.; Michael, Olugbenga S.
Graphical abstract: Highlights: Diabetes mellitus (DM) induces renal toxicity (RT). RT is associated with renal lipid deposition and inflammatory pathway. Elevated XO triggers RT in DM. Sodium acetate alleviates RT-associated with DM by suppression of XO. Abstract: Impaired renal function is a common complication of diabetes mellitus (DM) that often degenerates to cardiovascular disease, contributing to high morbidity and reduced survival worldwide. Short chain fatty acids (SCFAs), including acetate has shown potential benefits in glycemic or metabolic regulation but its effect on diabetes-associated renal toxicity/impairment is not clear. Herein, we investigated the hypothesis that acetate would ameliorate renal toxicity, accompanying DM, possibly by suppression of xanthine oxidase (XO) activity. Adult male Wistar rats (230–260 g) were allotted into groups (n = 6/group) namely: control (vehicle; po ), sodium acetate (NaAc)-treated (200 mg/kg), diabetic with or without NaAc groups. DM was induced by intraperitoneal injection of streptozotocin 65 mg/kg after a dose of nicotinamide (110 mg/kg). Diabetic animals showed increased fasting glucose and insulin, renal triglyceride, total cholesterol, atherogenic lipid, malondialdehyde, XO, tissue necrosis factor-α, uric acid, interleukin-6, aspartate transaminase/alanine aminotransferase ratio, gamma-glutamyl transferase and decreased glutathione and nitric oxide concentration. The renal tissue was characterized with disrupted tissue architecture, enlarged Bowman's space, congested glomeruli and adherence of abnormal segments of tuft to Bowman's capsule with consequent elevated serum creatinine and urea concentration. However, these alterations were attenuated by NaAc. The study demonstrates that acetate ameliorates diabetes-induced nephrotoxicity, which is associated with suppressed XO and its accompanied pro-inflammatory mediators. Therefore, SCFAs, acetate would be a promising dietary-derived therapeutic agent for the prevention and management of diabetes-associated renal disturbances.